Development of science learning e-module by using authentic learning experience model for the seventh graders - Suhatri, Desna; Hidayati, Abna; Bentri, Alwen; Zuwirna, Zuwirna (Indonesian Research Journal in Education |IRJE|, 2025)
This research determined which e-module for science learning uses the Authentic Learning Experiences (ALE) model. This research used research and development (R&D) as test subjects. Data collection techniques included learning material validation sheets, learning model validation, learning outcome tests, and teacher response questionnaires. Data analysis in this research was conducted using qualitative and quantitative analysis methods. The research results were: 1) A science learning e-module was produced by using the authentic learning experiences (ALE) model for the grade VII students with a very valid category. 2) The practicality of the science learning e-module, which uses the Authentic Learning Experiences (ALE) model to teach changes in substances, is demonstrated by observers’ evaluations of teachers rated as excellent. Science learning tools are stated to be very practical. 3) The effectiveness of using science learning e-modules, which employ the Authentic Learning Experiences (ALE) model is assessed through student activities and learning outcomes.